The natural history of canine occult Grade II medial patellar luxation: an observational study. (31st January 2020) - Hamilton, L.; Farrell, M.; Mielke, B.; Solano, M.; Silva, S.; Calvo, I.
Abstract : Objectives: To determine the risk of lameness and the rate of subsequent medial patellar luxation surgery in dogs that present with occult Grade II medial patellar luxation. Materials and methods: Retrospective owner survey and review of clinical records of adult dogs diagnosed with Grade II medial patellar luxation that were initially asymptomatic and managed non‐surgically that had a minimum of 4‐year follow‐up. Clinical notes and owner questionnaires identified dogs that subsequently developed lameness and required surgery on the previously asymptomatic stifle. Results: Thirty‐eight dogs were included with an average follow‐up of 51 months. Seventeen dogs re‐presented for unscheduled contralateral medial patellar luxation surgery at an average of 15 months after initial presentation. A further two dogs had chronic contralateral limb lameness after an average of 33 months after initial surgery and may have been potential surgical candidates. Clinical Significance: Fifty percent of adult dogs presenting with occult Grade II medial patellar luxation subsequently developed chronic lameness or required surgery.